Different prescribed doses of high-volume peritoneal dialysis and outcome of patients with acute kidney injury. - Ponce, Daniela; Brito, Germana Alves; Abrão, Juliana Maria Gera [UNESP]; Balb, André Luis (My University, 2011)
The optimal dialysis dose for the treatment of acute kidney injury (AKI) is controversial. No studies have directly examined the effects of peritoneal dialysis (PD) dose on outcomes in AKI. From January 2005 to January 2007, we randomly assigned critically ill patients with AKI to receive higher- or lower-intensity PD therapy (prescribed Kt/Vof 0.8 and 0.5 per session respectively). The main outcome measure was death within 30 days. Of the 61 enrolled patients, 30 were randomly assigned to higher-intensity therapy, and 31, to a lower-intensity PD dose. The two study groups had similar baseline characteristics and received treatment for 6.1 days and 5.7 days respectively (p = 0.42). At 30 days after randomization, 17 deaths had occurred in the higher-intensity group (55%), and 16 deaths, in the lower-intensity group (53%, p = 0.83). There was a significant difference between the groups in the PD dose prescribed compared with the dose delivered (higher-intensity group: 0.8 vs. 0.59, p = 0.04; lower-intensity group: 0.5 vs. 0.49, p = 0.89). The groups had similar metabolic control after 4 PD sessions (blood urea nitrogen: 69.3 +/- 14.4 mg/dL and 60.3 +/- 11.1 mg/dL respectively, p = 0. 71). In critically ill patients with AKI, an intensive PD dose did not lower the mortality or improve the recovery of kidney function or metabolic control. The PD dose is limited by dialysate flow and membrane permeability, and clearance per exchange can decrease if a shorter dwell time is applied.
Keywords: acute kidney failure; aged; clinical trial; controlled clinical trial; controlled study; female; human; male; methodology; middle aged; mortality; outcome assessment; peritoneal dialysis; randomized controlled trial; survival rate; Acute Kidney Injury; Aged; Female; Humans; Male; Middle Aged; Outcome Assessment (Health Care); Peritoneal Dialysis; Survival Rate